The Role of Qur'an Memorization in Enhancing Emotional and Spiritual Intelligence - Hakim, Addin Nur; Chusniatun, Chusniatun; Shohib, Muhammad Wildan (Universitas Muhammadiyah Surakarta, 2025)
The enhancement of emotional and spiritual intelligence among students presents a significant challenge in education today. One of the methods believed to significantly contribute to the development of both aspects is the duration of Qur'an memorization. However, there has been limited research specifically examining the effect of the duration of Qur'an memorization on emotional and spiritual intelligence, particularly in formal and non-formal educational settings. This study aims to examine the impact of the duration of Qur'an memorization on emotional and spiritual intelligence among students at Muhammadiyah Junior High School 1 Surakarta and Darul Ihsan Muhammadiyah Islamic Boarding School in Sragen. The research method employed is a quantitative approach with simple linear regression analysis to assess the relationship between memorization duration and both intelligence variables. The results show that the duration of Qur'an memorization has a significant influence on both emotional and spiritual intelligence, with a very large contribution at Muhammadiyah Junior High School 1 Surakarta (R² = 99.6% for emotional intelligence and R² = 99.7% for spiritual intelligence). At Darul Ihsan Islamic Boarding School, the duration of memorization significantly contributed to spiritual intelligence (R² = 97.4%), but its influence on emotional intelligence was only partially significant. The implications of these findings highlight the importance of integrating the Tahfidz program into the educational curriculum for character development and the need for enriched teaching methods in Islamic boarding schools to deepen students' emotional and spiritual intelligence.